Formation of The Mythologeme “Asia” In the Aspect of Analysis of Genre Characteristics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article provides an analysis in the aspect of studying genre characteristics in the formation of the mythology "Asia". The correlation of the national topos with the topos of the entire country illustrates the connection with the previous tradition, since with the accuracy of spatial designations a fantastic whole arises.